2009
DOI: 10.2134/agronj2008.0080x
|View full text |Cite
|
Sign up to set email alerts
|

Dryland Crop Yields and Soil Organic Matter as Influenced by Long‐Term Tillage and Cropping Sequence

Abstract: A gronomy J our n al • Volume 101, I s sue 2 • 2 0 0 9 ABSTRACT Novel management practices are needed to improve the declining dryland crop yields and soil organic matter contents using conventional farming practices in the northern Great Plains. We evaluated the 21-yr eff ect of tillage and cropping sequence on dryland grain and biomass (stems + leaves) yields of spring wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and pea (Pisum sativum L.) and soil organic matter at the 0-to 20-cm depth in east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 43 publications
7
84
1
Order By: Relevance
“…Although information is available about the use of improved management practices to increase C sequestration in dryland soils (Halvorson et al, 2002;Sainju et al, 2009Sainju et al, , 2011, relatively little is known about GHG emissions from agricultural practices. Some of the management practices that aff ect CO 2 , N 2 O, and CH 4 emissions in dryland soil are tillage, cropping system, and N fertilization (Curtin et al, 2000;Lemke et al, 1999;Sainju et al, 2010).…”
Section: Dryland Soil Greenhouse Gas Emissions Affected By Cropping Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although information is available about the use of improved management practices to increase C sequestration in dryland soils (Halvorson et al, 2002;Sainju et al, 2009Sainju et al, , 2011, relatively little is known about GHG emissions from agricultural practices. Some of the management practices that aff ect CO 2 , N 2 O, and CH 4 emissions in dryland soil are tillage, cropping system, and N fertilization (Curtin et al, 2000;Lemke et al, 1999;Sainju et al, 2010).…”
Section: Dryland Soil Greenhouse Gas Emissions Affected By Cropping Smentioning
confidence: 99%
“…Total CO 2 equivalents of GHGs, averaged across years, amounted to 1.27, 1.28, 1.42, 1.63, 1.54, 1.61 Mg CO 2 -C ha -1 for CTB-F with 0 kg N ha -1 , CTB-F with 80 kg N ha -1 , NTB-P with 0 kg N ha -1 , NTB-P with 80 kg N ha -1 , NTCB with 0 kg N ha -1 , and NTCB with 80 kg N ha -1 , respectively. Although CTB-F with 0 and 80 kg N ha -1 produced lower CO 2 equivalents of GHGs than other management practices, fallowing in CTB-F reduces annualized crop yield and soil organic matter (Lenssen et al, 2007;Sainju, 2008;Sainju et al, 2009) and becomes unsustainable and uneconomical (Aase and Schaefer, 1996). Because of the intermediate level of CO 2 equivalent of GHGs, NTB-P with 0 kg N ha -1 might be used as a management option to mitigate GHG emissions under dryland cropping systems.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Increasing this input (e.g., leaving straw to mulch, continuous cropping), together with management practices that reduce soil aeration, could, however, enhance SOM accumulation Halvorson et al, 2002). However, in semiarid environments, experiments have shown that the tillage practice can affect SOM accumulation (and indeed other soil properties), the outcome is highly site-specific (Ordóñez Fernández et al, 2007;Thomas et al, 2007;Hernanz et al, 2009; Influence of tillage practices on soil biologically active organic matter content over a growing season under semiarid Mediterranean climate Sainju et al, 2009). While some authors report notillage to have a beneficial effect on SOM accumulation (López-Fando & Pardo, 2009;Sombrero & De Benito, 2010), others indicate it to have little or no impact (Thomas et al, 2007;Sainju et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the fallow period by reducing the cropping intensity can reduce soil water storage efficiency and SOM while enhancing saline seeps development (Tanaka and Aase, 1987;Black and Bauer, 1988). In contrast, reducing tillage and increasing cropping intensity can increase crop yields and SOM (Aase and Pikul, 1995;Halvorson et al, 2002;Sainju et al, 2009b).…”
mentioning
confidence: 99%
“…Traditional dryland farming practices with conventional tillage and wheat-fallow systems in the northern Great Plains have reduced annualized crop yields and SOM due to the absence of crops during the fallow period and increased soil erosion and C and N mineralization (Aase and Pikul, 1995;Halvorson et al, 2002;Sainju et al, 2009b). While intensive tillage increases the oxidation of SOM (Bowman et al, 1999;Schomberg and Jones, 1999), fallowing reduces it by reducing the amount of crop residue returned to the soil and increasing soil temperature and water content, which subsequently increase microbial activity (Campbell et al, 2000;Halvorson et al, 2002).…”
mentioning
confidence: 99%